ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VII SMP NEGERI 65 MALUKU TENGAH PADA MATERI SUHU DAN KALOR - Wilem Rilexen S P Mulder; Joko Siswanto (Universitas Tanjungpura, 2023)
This research aims asa preliminary study to determine the ability to think creatively in physics learning using a correlational form with a quantitative approach and analyzed descriptively. The research subject is class VII SMP Negeri 65 Central Maluku, Central Maluku Regency. The data collection stage uses a test instrument containing description questions that have been designed in line with creative thinking indicators. Based on the results of the study, the average score of students' creative thinking skills was 54.94. with a high percentage of 1 student (5.89%). 11 students (70.59%) moderate, and 4 students (23.52%) low with the achievement level of each indicator 95% Fluency, 70% Flexibility, 75% Originality, 68% Elaboration, and 66% Evaluation. The conclusions of this study indicate the tendency of students' creative thinking abilities to be in the medium and low categories. The implication of this preliminary study is that physics learning media will be developed by utilizing technology by STEM-based interactive web with ESD insight on temperature and heat material to improve students' creative thinking skills